Addressing vitamin-A and micronutrient deficiency issues through culture of mola, Amblypharyngodon mola with carps - Nayak, Suchismita; Radhakrishnan, Kalidoss; Verma, Dhananjay Kumar; Das, Krushna Chandra; Routray, Padmanav (Journal of the Inland Fisheries Society of India, 2021)
The present study aimed to evaluate the growth and production performance of mola, Amblypharyngodon mola in monoculture and in polyculture with carps to produce a higher amount of quality fish protein. For this, hatchery bred mola was used for the first time and the experiment was categorized into three treatments viz., T1-monoculture, T2-IMC with 300 nos. of mola, and T3-IMC with 400 nos. of mola in polyculture in duplicate. The IMC fingerlings and mola were fed with commercial floating pellets and powdered feed respectively. The overall production in T1, T2 and T3 were 199 kg ha-1, 266 kg ha-1 (185 kg IMC + 81 kg mola) and 277 kg ha-1 (183 kg IMC + 94 kg mola) respectively. Production of Labeo catla increased with higher stocking densities of mola whereas no remarkable growth differences were noticed for Labeo rohita and mola in carp-mola polyculture. The benefit-cost ratio was found to be highest in carp-mola polyculture than the monoculture of mola, suggesting that carpmola polyculture is economically viable. Here the total biomass production of mola was less compared to rohu in polyculture ponds, however, the estimated contribution of vitamin A (IU/100g) to human diet was manifold i.e. 196 and 240 times more than the carps (that is actually produced). This study is significant in terms of the polyculture of mola with carps and may address the issues of vitamin-A and micronutrient deficiency in the future Key words Ecosystem, economics, hatchery bred, monoculture, polyculture